Time elapsed between ovulation and insemination determines the quality of fertilized rat oocytes - Naomi NAKAGATA; Satohiro NAKAO; Nobuyuki MIKODA; Katsuma YAMAGA; Toru TAKEO (The Society for Reproduction and Development, 2024)
Genetically modified rats are valuable models in human disease research. We recently developed an improved system for rat sperm cryopreservation and in vitro fertilization (IVF) that facilitates the efficient production and preservation of genetically modified rats. In the IVF procedure performed using frozen-thawed rat sperm, the IVF schedule is fixed to ensure timely hormone administration and oocyte collection. To enhance the flexibility of the IVF schedule, possible periods of postovulated rat oocytes with normal fertility and developmental abilities should be determined. Therefore, in this study, we examined the fertilization and developmental ability of incubated oocytes 1-13 h after oocyte collection at 9:00 AM. The fertilization rate decreased 7 h after oocyte collection, and abnormally fertilized oocytes appeared 10 h after oocyte collection. The developmental rate also decreased 7 h after oocyte collection; however, live pups were obtained from oocytes 12 h after oocyte collection. In summary, ovulated rat oocytes exhibited a high developmental ability after IVF for up to 4 h after oocyte collection.